Perbandingan Stroke Non Hemoragik dengan Gangguan Motorik Pasien Memiliki Faktor Resiko Diabetes Melitus dan Hipertensi - Nia Permatasari (Jurnal Ilmiah Kesehatan Sandi Husada, 2020)
Background: Stroke in Indonesia has also increased in prevalence. In Indonesia, this disease ranks third after heart disease and cancer. In 2007, the results of the Basic Health Research (Riskesdas) showed data 8.3 per 1000 population suffered a stroke. Stroke was also the main cause of death in almost all hospitals in Indonesia, which amounted to 14.5%. Purpose: To find out how Comparison of Motor Disorders in Non-Hemorrhagic Stroke Patients with Risk Factors for Diabetes Mellitus, Hypertension, Diabetes Mellitus & Hypertension in RSUD Dr. H. Abdul Moeloek Lampung Province in 2018. Methods: The design of this study was descriptive-analytic with cross-sectional approach. The subjects of this study were all patients with motor disorders in non-hemorrhagic stroke with risk factors for diabetes mellitus, hypertension, diabetes mellitus and hypertension in RSUD Dr. H. Abdul Moeloek Lampung Province. Result: The study sample was 30 patients. Non-hemorrhagic stroke in hypertensive patients as much as (92.6%), non-hemorrhagic stroke in patients with diabetes mellitus (81.5%), non-hemorrhagic stroke in hypertensive patients and diabetes mellitus as much as (74.1%). By using the Kolmogorov-Smirnov Z test the significant value is 0.280 (p = 0.280> α = 0.05) then Ho is accepted.Conclusion: There is no comparison of hypertension in non-hemorrhagic stroke with mild and moderate motor disturbances at Dr.H. Abdul Moeloek Lampung Province in 2018.